Der gute POL-Tutor - sein oder nicht sein: Lehrfilme für Tutoren = The good PBL tutor - to be or not to be : instructional films for tutors - Skelin, Silvia Maria; Huwendiek, Sören; Nikendei, Christoph; Dieter, Peter; Kirschfink, Michael; Bosse, Hans-Martin (Zeitschrift für Evidenz, Fortbildung und Qualität im Gesundheitswesen, 2008)
INTRODUCTION: Many faculties worldwide apply the method of problem-based learning (PBL) in their curricula as a form of instruction by which students in small groups develop problem-solving strategies on the basis of a specific case. This approach fosters self-responsible and context-dependent learning, which aims at providing an improved anchoring of knowledge. For this reason, the previous decades have seen a distribution of the method to medical schools across the world. The role of the tutor assumes particular importance since, in contrast to the traditional university system, he or she serves as a facilitator who fosters and structures content-related and group-dynamic learning processes. In some cases, this requires an intervention by the tutor. The major challenge is to intervene at the right time and in an appropriate manner. METHOD: This paper presents examples of difficult PBL situations using short film sequences to demonstrate and comments on potential approaches of the tutor in attempting to resolve the problem. Standard problem situations within a PBL tutorial were defined and produced in a film. RESULTS: A collection of seven frequent critical PBL situations are presented in short film sequences. Potential instruments of intervention are demonstrated in the videos and discussed. The film sequences may be downloaded in the supplementary of the electronic version of this article (www.sciencedirect.com). CONCLUSION: Within the framework of a tutor-training programme, the problematic situations and interventions presented in this article will help to sensitise tutors to potentially critical PBL tutorial situations and aid the development of individual resolution approaches.
Gesehen am 21.06.2021